DIGITAL STORYTELLING: NARRATIVE TECHNIQUES IN ONLINE LITERATURE - Xojabekova , Ramzida (Scientific practical conference, 2026)
This article explores digital storytelling and its narrative techniques within online literature, emphasizing how multimedia, interactivity, and non-linear structures reshape contemporary storytelling. It examines the use of text, images, audio, video, hyperlinks, and interactive elements to create immersive narrative experiences. The study discusses audience engagement, participatory culture, genre experimentation, and the pedagogical potential of digital storytelling. Challenges such as technical limitations, platform constraints, narrative coherence, and preservation are also considered. The article concludes that digital storytelling transforms the relationships between authors and audiences, expands creative possibilities, and provides a framework for understanding narrative innovation in the digital age.